Integrasi Pendaftaran Tanah dengan Penataan Ruang Padat Penduduk dalam Mencegah Konflik Agraria - Gayatri Natha Sandi; Kayla Nurhaliza Kadir; Naswa Ulaya Putri Prasna; Muhammad Syihabul Fikri Haiban; Aprila Niravita; Muhammad Adymas Hikal Fikri (JURNAL ILMIAH NUSANTARA, 2026)
Agrarian conflict in densely populated areas is a persistent structural problem in Indonesia, fueled by a weak land registration system and a misalignment between spatial use and land ownership rights. This study aims to analyze the urgency of integrating land registration and spatial planning as an instrument for preventing agrarian conflict in densely populated areas. Using normative legal research methods and a legislative and conceptual approach, this study examines the legal framework governing land registration and spatial planning in Indonesia and identifies regulatory gaps that are at the root of agrarian conflict. The results indicate that systematically integrating land spatial data with regional spatial plans (RTRW) can minimize overlapping land ownership, provide legal certainty for communities, and create fair and sustainable land governance. Regulatory reform, institutional capacity building, and database synchronization between the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (BPN) and local governments are needed as concrete steps to realize this integration.